Enhanced heterologous protein production in Pichia pastoris under increased air pressure. (6th August 2014) - Lopes, Marlene; Oliveira, Carla; Domingues, Lucília; Mota, Manuel; Belo, Isabel
<x xml:space="preserve">Abstract</x> Pichia pastoris is a widely used host for the production of heterologous proteins. In this case, high cell densities are needed and oxygen is a major limiting factor. The increased air pressure could be used to improve the oxygen solubility in the medium and to reach the high oxygen demand of methanol metabolism. In this study, two P. pastoris strains producing two different recombinant proteins, one intracellular (β‐galactosidase) and other extracellular (frutalin), were used to investigate the effect of increased air pressure on yeast growth in glycerol and heterologous protein production, using the methanol AOX1‐inducible system. Experiments were carried out in a stainless steel bioreactor under total air pressure of 1 bar and 5 bar. The use of an air pressure raise of up to 5 bar proved to be applicable for P. pastoris cultivation. Moreover, no effects on the kinetic growth parameters and methanol utilization (Mut) phenotype of strains were found, while an increase in recombinant β‐galactosidase‐specific activity (ninefold) and recombinant frutalin production was observed. Furthermore, the air pressure raise led to a reduction in the secreted protease specific activity. This work shows for the first time that the application of an air pressure of 5 bar may be used as a strategy to decrease protease secretion and improve recombinant protein production in P. pastoris. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 30:1040–1047, 2014